Politik Bahasa Asing dan Hegemoni Pesantren di Nusantara - Wahyu Hanafi Putra; Rizki Amalia Sholihah (Study Program of Arabic Language Teaching, 2020)
This study aims to describe the role of foreign languages as a medium for the development of pesantren in the archipelago. The research method used is descriptive qualitative. Pesantren is one of the oldest Islamic educational institutions in Indonesia. In the history of its development, pesantren reap some barriers, until finally at the beginning of XX century pesantren began to demand by many people. The success of pesantren in managing Islamic education is partly because of the role of foreign languages (Arabic and English) taught in it. In the globalization era, foreign language is a primary requirement for students, thus making pesantren as an alternative institution in developing foreign language skills of santri, in addition, the learning of foreign languages in pesantren is more effective because of the language environment. This is one of them can make foreign language as one of the political media in order to advance the existence of pesantren. Foreign language politics in pesantren means managing foreign languages as the language of communication in various policies in pesantren. Some pesantrens in Indonesia with a background of modern pesantren and Salāf pesantren are keen to utilize foreign languages as a means of communication, resistance, and reconstruction of pesantren, such as the modern pesantren Gontor Ponorogo, Darullughah Wadda'wah Bangil Pasuruan pesantren, and Sidogiri Pasuruan pesantren. Some of these pesantren are pesantren who successfully manage foreign languages in accordance with the above functions. Thus, the paradigm of pesantren succession is not only seen from the number of santri who are proficient in Islamic Studies, but also from the extent to which santri skilled in various fields, one of which is foreign language.